Dynamics of affect, cognition and behavior in a general population sample of adolescents and young adults with current and remitted anxiety disorders: An Ecological Momentary Assessment study. (January 2023) - Seidl, Esther; Venz, John; Ollmann, Theresa Magdalena; Voss, Catharina; Hoyer, Jana; Pieper, Lars; Beesdo-Baum, Katja
Abstract: Background: Measures of dynamic changes in affect/emotions (variability, instability, inertia) have been linked to anxiety disorders (AD). We examine dynamics in affect, cognition and behavior in youth with current and remitted AD. Methods: Mental disorders were assessed in a general population sample (N = 1180, age 14–21; Dresden, Germany) using standardized interview. Ecological Momentary Assessment of real-life affect, cognition and behavior took place eight times/day for four days. Results: Individuals with current AD (n = 65) compared to healthy controls (HC, n = 531) revealed heightened variability of anxious and manic symptomatology, experiential avoidance, optimism and positive thoughts. Remitted AD (n = 52) showed lower variability of anxious and manic symptomatology and positive thoughts compared to current AD, while no differences were found compared to HC. Current AD and HC differed significantly in instability. Remitted AD showed lower instability of all constructs except for anger than current AD, and higher instability on all constructs except for positive and negative thoughts compared to HC. Current AD showed higher inertia of anger and negative thoughts than HC, and less inertia of positive thoughts than remitted AD. Discussion: AD in youths is particularly linked to higher variability and instability of intertwined emotion-related experiences that partly persist after remission, informing emotion regulation models and interventions. Highlights: Differences in daily life experience in youth with and without anxiety disorder. Higher variability in current anxiety disorders vs healthy controls. Higher instability in current anxiety disorders vs healthy controls. Lower instability in remitted anxiety disorders vs current anxiety disorders. Higher instability in remitted anxiety disorders vs healthy controls.